Comparative Analysis on the Effectiveness of Fashion Trends Set by Hollywood and Nollywood Stars on Students - Omolara Akin-Odukoya; Funmi Falobi; Omotola Ogunbola; Balogun Oluwapelumi Kafayat; Muhammad Ridwan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2024)
The studies delve into the Comparative Effectiveness of Fashion Trends set by Hollywood and Nollywood stars on Student. It’s objectives is to analyze the extent to which Hollywood and Nollywood Fashion trends affect students purchasing choices and Personal style .The Magic Bullet Theory and Social Learning Theory were the theories employed for this project and data from this study was obtained through questionnaire which was distributed among 200 students of different departments in the university of Lagos . The findings reveal that Hollywood fashion trends significantly influence students’daily attire and personal style with notable portion of respondents incorporating these trends into their wardrobe. The study recommends that schools and universities should encourage discussion around the psychological and social aspects of fashion consumption, fostering a balanced and healthy approach to fashion among students.